STRUCTURAL PRODUCT AS A TOOL FOR MANAGING PROBLEM DEBT - N. V. Gryzunova (Вестник университета)
Bad debts have been an ever-increasing threat to the Russian banking sector over the past decade. Currently, the number of problem debtors has stabilized, and the amount of debt has become classified. The policy of the regulator protects the debtor, this is due to extremely high interest rates on loans. The growth of bad debt is a kind of market reaction to inadequate rates. Today, the most important problem for credit organizations and for their customers is the repayment of loans and loans on conditions adequate to the economic situation. In this regard, researchers discuss the problems of creating a mechanism for the settlement of problem debts based on legal guarantees, portfolio technologies, control of retail pricing in the credit market and risk management. For debtors, the possibilities of debt restructuring have recently expanded, in particular, it is possible to use a wide range of financial instruments: subordinated bonds and structured products. The purpose of the article is to determine universal rules for managing bad debts using financial instruments - bonds and structural products, which will help create conditions for long-term financial stability.